Genomics in Endangered Species Conservation: A Bibliometric Analysis - Loso Judijanto (West Science Nature and Technology, 2026)
This study presents a bibliometric analysis of research on genomics in endangered species conservation to map its intellectual structure, thematic evolution, and global collaboration patterns. Data were analyzed using bibliometric visualization techniques to identify keyword co-occurrence, thematic clusters, density distributions, co-authorship networks, institutional affiliations, and country-level collaborations. The results show that genomics and endangered species constitute the central knowledge base of the field, strongly connected with genetics, population genetics, and conservation genomics. Thematic evolution indicates a shift from traditional molecular genetics and phylogenetic studies toward high-throughput genomic approaches, particularly population genomics and single nucleotide polymorphism (SNP)-based analyses. Collaboration network analysis reveals a globally distributed but centralized structure, dominated by major research hubs such as the United States and China, with strong supporting contributions from Europe and emerging participation from developing regions.